Anti-Fascist Themes and Reflection of Second World War Events in Soviet Animated Cartoons in 1933–1944 - Borodin, G. N. (Телекинет)
The author reconstructs the history of the production of animated films just before and during the Great Patriotic War and clarifies information about lost films and about films that were in the works of animation associations and the Soyuzmultfilm studios. The article examines the thematic plan, calendar schedule, documents and evidence, thanks to which the life of Soviet animation of the specified period is reconstructed. The author reconstructs the history of the films A Little Story about a Big Soap Bubble, Crazy Flight, A Midsummer Night’s Dream, Barmaley, Titmouse, Von Grabbe, etc. Valuable factual material is examined in chronological order, in several stages, and each of them allows one to form a complete impression of how Soviet animation responded to foreign policy events before 1941 and during the war. Folklore narratives came to the aid of filmmakers; for example, the plot of The Turnip was extrapolated by filmmakers to the current situation: the USSR played the role of the vegetable, while Hitler acted as the grandfather; The Song of Chapaev was made in an unusual genre — a film-song. The author analyzes applications and scripts and introduces in scientific discourse plots and films of various genres, including instructional films.